ANALISIS SISTEM PENYAMPAIAN JASA PADA TOKO BUKU GRAMEDIA PALEMBANG DAN TOKO BUKU KHARISMA PALEMBANG - Ninin Non Ayu Salmah (Universitas PGRI Palembang, 2013)
This research aims to know the respond of customers about delivery service system in Gramedia Book Store and Kharisma Book Store Palembang and whether the differences of system system from those book stores exist. This research is analytical descriptive survey which means the data were gathered upon an object in the field by taking samples from particular population and using questionnaire as the media to gather the information. The type of research is causally comparative in which to compare the variables of each object. The data used was a cross-sectional data which illustrated the condition of certain time. The populationThe population used was the customers of both book stores which had ever gotten the services from them more than twice.The research resulted that there were no significant differences of system from both book stores. Keywords : service delivery system, physical support, contact personnel